β‐Adrenergic Blockers - Frishman, William H. (J Clin Hypertens (Greenwich), 2011)
J Clin Hypertens (Greenwich). 2011;13:649–653. ©2011 Wiley Periodicals, Inc. KEY POINTS AND PRACTICAL RECOMMENDATIONS: •  β‐Blockers are appropriate treatment for patients with hypertension and those who have concomitant ischemic heart disease, heart failure, obstructive cardiomyopathy, or certain arrhythmias. •  β‐Blockers can be used in combination with other antihypertensive drugs to achieve maximal blood pressure control. Labetalol can be used in hypertensive emergencies and urgencies. •  β‐Blockers may be useful in patients having hyperkinetic circulation (palpitations, tachycardia, hypertension, and anxiety), migraine headache, and essential tremor. •  β‐Blockers are highly heterogeneous with respect to various pharmacologic effects: degree of intrinsic sympathomimetic activity, membrane‐stabilizing activity, β(1) selectivity, α(1)‐adrenergic–blocking effect, tissue solubility, routes of systemic elimination, potencies and duration of action, and specific effects may be important in the selection of a drug for clinical use. •  β‐Blocker usage to reduce perioperative ischemia and cardiovascular complications may not benefit as many patients as was once hoped and may actually cause harm in some individuals. Currently the best evidence supports β‐blocker use in two patient groups: patients undergoing vascular surgery with known ischemic heart disease or multiple risk factors for it and for patients already receiving β‐blockers for known cardiovascular conditions.